2016
DOI: 10.14348/molcells.2016.0014
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis of Drosophila Regulatory Peptide Expression in Enteroendocrine Cells

Abstract: The digestive system is gaining interest as a major regulator of various functions including immune defense, nutrient accumulation, and regulation of feeding behavior, aside from its conventional function as a digestive organ. The Drosophila midgut epithelium is completely renewed every 1–2 weeks due to differentiation of pluripotent intestinal stem cells in the midgut. Intestinal stem cells constantly divide and differentiate into enterocytes that secrete digestive enzymes and absorb nutrients, or enteroendoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 40 publications
1
50
0
Order By: Relevance
“…First, to unambiguously assess the main source of Bursα production during adulthood, we compared mRNA expression levels in mature whole adults, adult midguts, and adult animals from which the gut was removed prior to RNA extraction (“gut-less”). Confirming our previous results ( Scopelliti et al., 2014 , Scopelliti et al., 2016 ) and subsequent independent reports ( Chen et al., 2016 , Dutta et al., 2015 ), we observed strong enrichment of bursα transcripts in adult midguts ( Figure 1 A).
Figure 1 Bursα in ee Cells Is Regulated by Nutrients (A and C) Transcript levels of bursα relative to rpl32 in indicated tissue samples from 10- to 14-day-old adult wild-type animals (A) or whole midguts from animals of the indicated genotypes (C).
…”
Section: Resultssupporting
confidence: 93%
“…First, to unambiguously assess the main source of Bursα production during adulthood, we compared mRNA expression levels in mature whole adults, adult midguts, and adult animals from which the gut was removed prior to RNA extraction (“gut-less”). Confirming our previous results ( Scopelliti et al., 2014 , Scopelliti et al., 2016 ) and subsequent independent reports ( Chen et al., 2016 , Dutta et al., 2015 ), we observed strong enrichment of bursα transcripts in adult midguts ( Figure 1 A).
Figure 1 Bursα in ee Cells Is Regulated by Nutrients (A and C) Transcript levels of bursα relative to rpl32 in indicated tissue samples from 10- to 14-day-old adult wild-type animals (A) or whole midguts from animals of the indicated genotypes (C).
…”
Section: Resultssupporting
confidence: 93%
“…Second, DH31 has been implicated in the control of visceral muscle peristalsis and motility in Drosophila larvae [ 33 , 34 ]. Third, although DH31 is expressed in many EECs located in the posterior adult midgut, the expression of DH31 has been detected in few anterior EECs in the adult midgut [ 35 , 36 ]. Fourth, two transcriptomic analyses in the Drosophila midgut revealed that the DH31 receptor-encoding gene (DH31-R ) [ 37 ] is expressed in the anterior region of visceral muscle [ 38 , 39 ] ( http://flygut.epfl.ch ; http://flygutseq.buchonlab.com ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally DILP3 is produced by intestinal muscle cells ( Veenstra et al, 2008 ) and sparse bursicon expression was seen in some EECs ( Scopelliti et al, 2014 ). In EECs of the anterior and middle midgut TK and NPF are colocalized, in the midportion orcokinin B and allatostatin C, and in the posterior end TK and DH31 ( Figure 9A ) ( Veenstra et al, 2008 ; Veenstra and Ida, 2014 ; Chen et al, 2016a ). Of note is that in the larval gut anteriorly located MIP producing EECs were shown to also express Cha, suggesting that they produce acetylcholine, which may act in paracrine signaling ( LaJeunesse et al, 2010 ).…”
Section: Colocalization Of Peptides In Intestinal Endocrine Cellsmentioning
confidence: 99%